Nutritional Status among pediatric Age Group with Chronic Renal Failure undergoing Hemodialysis - Sarra Abumaeza; Aisha Alharari; Hawa Abumaeza (African Journal of Advanced Pure and Applied Sciences, 2025)
Background: Recently, food poisoning has become a growing public health problem worldwide, in both developed and developing countries. In developing countries, poor knowledge about food handling, safety, and hygiene may cause food-borne diseases. Objective: to assess the knowledge, attitude, and practices (KAP) of food safety awareness among the public Libyan population. Material and methods: A cross-sectional study was conducted on a random sample of hundred adult (male& symptoms of food poisoning (p value = 0.020female) from the public in Tripoli. The study period was from September 2022 to Nov 2023. The study was carried out using a face-to-face questionnaire in Arabic The questionnaire consisted of two parts: personal information, knowledge, attitude & Practice of food safety. The data analysis was performed using the Statistical Package for the Social Sciences (SPSS), Version 24.0. Descriptive statistics were conducted to determine the means, percentages, standard deviations, and frequencies. chi-square test (X2) was used to determine the association of knowledge and practices with demographics. The Results: Our study found that the subjects were between the ages of 18-35 years (65.0%). Most respondents were males (75%). 43.0% of participants had a university degree, which is the majority. Out of 100 participants, 75 percent had great awareness of food poisoning, and 43% of them felt abdominal cramps, which are indications of food poisoning. The majority of respondents had medium income levels, with their percentage being 69.0%. However, there was a significant difference in knowledge, attitude, and practice about food poisoning (p values = 0.003, 0.004, 0.041, and 0.048, respectively), as well as a substantial correlation between educational level and understanding of the symptoms of food poisoning (p value = 0.020).